Contribuição ao entendimento da patogenia da sepse - Fracasso, J. F. [UNESP] (My University, 2008)
The most frequent cause of vasodilatory shockis outcome from sepsis, a systemic inflammatory response to infection, characterized by hypotension, hyporeactivity to the catecholamines and disseminated intravascular coagulation. The commonest cause of sepsis has reported to be infection with Gram-negative bacteria, typically E. coli, resulting in the release of lipopolysaccharide (endotoxin) from the bacterial outer membrane during autolysis or death of these microorganisms, with the involvement of many mediators, including nitric oxide. Later it was found that plasma levels of vasopressin in sepsis patients were abnormally low and observed that some patients with advanced septic shock were extremely sensitive to the activity actions of exogenous vasopressin.

O choque vasodilatador mais freqüente resulta de sepse, uma inflamação sistêmica em resposta a uma infecção que se caracteriza por hipotensão, hiporreatividade às catecolaminas e coagulação intravascular disseminada. A causa mais comum de sepse é a infecção por bactérias Gram-negativas, principalmente de Escherichia coli, resultando na liberação de lipopolissacarídeos (endotoxinas) da parede celular, quando da morte ou lise do microrganismo, com o envolvimento de muitos mediadores, incluindo o óxido nítrico. Mais tarde descobriu-se que os níveis sanguíneos de vasopressina, em pacientes com sepse, eram anormalmente baixos, e observou-se que alguns destes pacientes, com choque séptico avançado, eram extremamente sensíveis às ações pressóricas da vasopressina exógena. Palavras-chave: endotoxina; vasopressina; choque séptico; sepse; hiporreatividade; choque vasodilatador.
A contribution to the understanding of the phatogenesis of sepsis
Keywords: Endotoxin; Hyporeactivity; Sepsis; Septic shock; Vasodilatory shock; Vasopressin; acetylsalicylic acid; catecholamine; dexamethasone; dobutamine; Escherichia coli endotoxin; glibenclamide; nitric oxide; noradrenalin; vasodilator agent; vasopressin; arterial pressure; autolysis; bacterial outer membrane; disseminated intravascular clotting; endothelium cell; Escherichia coli; Gram negative bacterium; Gram negative sepsis; human; hypotension; nonhuman; pathogenesis; sepsis; septic shock; vasopressin blood level